Wonder, Politics, and the Founding of Civilizations in Gravina’s Della Ragione Poetica and Vico’s Scienza Nuova - Bertland, Alexander (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
Gianvincenzo Gravina (1664–1718) and Giambattista Vico (1668–1744) were two Neapolitan philosophers concerned with the way human society initially formed. They agreed that ancient myths were produced by a mentality that had a powerful ability for acute perception but could not reflect abstractly. They also agreed that wonder (la maraviglia) was an important force that enchanted the first peoples into founding society. They disagreed on how this happened. Gravina argued that early poets could see the truth and used persuasive poetry to teach the people how to live. Vico argued that wonder impelled the first poets to create false divinities that frightened the first bestial people into founding civilization. While the two views differ, they show how Neapolitan Enlightenment thinkers developed radically different answers to questions that Northern Europeans were asking.